Transformação digital no varejo de alimentos: um estudo sobre a capacidade de adaptação em supermercados no RS - Bruschi, Gabriela Piasseta (Universidade do Vale do Rio dos Sinos, 2021)
This paper intends to understand the perceptions and which capabilities the small and medium sized food retail in the state of RS (Brazil) should improve upon digital transformation. For this, it was suggested a research dimension based on four categories: (1) Culture and Strategy; (2) Emerging Technologies and Processes; (3) Value Chain and (4) Capabilities and Resources Configuration. These dimensions were based in studies of Digital Transformation, Dynamic Capabilities and Marketing Capabilities. This research used a multi-method approach, using an exploratory quantitate survey and interviews with businessmen and marketing and retail specialists, which contributed to the understanding of the motivations, barriers, and opportunities to the small and medium sized food retail upon digital transformation. The results indicate an initial stage of digital development of the food retailers in the state of RS, once the changes upon the digital transformation are responsive and not part of the strategy of the companies and; concludes with a table of capabilities to be improved to reach a sustainable competitivity towards changing scenarios.
Keywords: Varejo de alimentos; Transformação digital; Capacidades dinâmicas; Capacidades de marketing; Food retail; Digital transformation; Dynamic capabilities; Marketing capabilities; ACCNPQ::Ciências Sociais Aplicadas::Administração